EVALUASI PEMERIKSAAN PSIKOMETRI PADA TATALAKSANA AWAL GANGGUAN CEMAS MENYELURUH DENGAN GANGGUAN DEPRESIF BERULANG: SEBUAH LAPORAN KASUS - PUTRA, I PUTU RISDIANTO EKA; MARIANTO, MARIANTO; SRIANDARI, LUH PUTU FEBY (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This case report discusses a 32-year-old female patient who presented with generalized anxiety disorder and recurrent depressive disorder, current episode severe without psychotic symptoms. The patient presented with complaints of excessive anxiety that had persisted for three years and had worsened in the last three months, accompanied by physical complaints such as heartburn, palpitations, and frequent feelings of fainting. In addition to anxiety, the patient also experienced depressive symptoms such as feelings of sadness, fatigue, sleep disturbances, and loss of interest in daily activities. The results of the mental status examination showed an anxious and sad mood with preoccupation with health problems. Psychodynamic assessment identified the presence of ego defense mechanisms such as repression and somatization related to past traumatic experiences and strict parenting. The diagnostic formulation led to a primary diagnosis of generalized anxiety disorder and recurrent depressive disorder, with anankastic and anxious-avoidant personality factors supporting the patient's clinical symptoms. The management provided included pharmacotherapy with sertraline, clobazam, and risperidone, as well as non-pharmacological interventions in the form of psychoeducation, supportive psychotherapy, relaxation, and psychodynamic psychotherapy. Family therapy was also applied to increase support from the husband and family. The patient's prognosis was dubia ad bonam, with aggravating factors in the form of immature ego defense mechanisms and less than optimal family support. This report highlights the importance of a holistic approach in the management of anxiety and depressive disorders involving psychotherapy and family support in addition to pharmacological therapy. ABSTRAKLaporan kasus ini membahas seorang pasien perempuan berusia 32 tahun yang mengalami gangguan cemas menyeluruh dan gangguan depresif berulang, episode kini berat tanpa gejala psikotik. Pasien datang dengan keluhan kecemasan berlebihan yang telah berlangsung selama tiga tahun dan semakin memburuk dalam tiga bulan terakhir, disertai keluhan fisik seperti nyeri ulu hati, berdebar-debar, dan sering merasa akan pingsan. Selain kecemasan, pasien juga mengalami gejala depresi seperti perasaan sedih, mudah lelah, gangguan tidur, dan kehilangan minat terhadap aktivitas sehari-hari. Hasil pemeriksaan status mental menunjukkan adanya mood cemas dan sedih dengan preokupasi terhadap masalah kesehatan. Penilaian psikodinamik mengidentifikasi adanya mekanisme pertahanan ego seperti represi dan somatisasi yang berkaitan dengan pengalaman traumatis masa lalu serta pola asuh yang ketat. Formulasi diagnostik mengarah pada diagnosis utama gangguan cemas menyeluruh dan gangguan depresif berulang, dengan faktor kepribadian anankastik dan cemas menghindar yang mendukung gejala klinis pasien. Penatalaksanaan yang diberikan meliputi farmakoterapi dengan sertraline, clobazam, dan risperidone, serta intervensi non-farmakologis berupa psikoedukasi, psikoterapi suportif, relaksasi, dan psikoterapi psikodinamik. Terapi keluarga juga diterapkan untuk meningkatkan dukungan dari suami dan keluarga. Prognosis pasien bersifat dubia ad bonam, dengan faktor pemberat berupa mekanisme pertahanan ego imatur dan dukungan keluarga yang kurang optimal. Laporan ini menyoroti pentingnya pendekatan holistik dalam manajemen gangguan cemas dan depresi yang melibatkan psikoterapi dan dukungan keluarga selain terapi farmakologi.